The Emergence of Non-Linear Theory in Human Resource Management - Thoha, Nurianna; Hutapea, Parulian (Jurnal Manajemen Teknologi, 2006)
this paper presents an empirical-study carried-out in Indonesia using seven-companies across private and public-sectors. The study set out to analyse human-resource-activities at three-levels: personel-administration (PA), human-resource-management (HRM) and strategic-human-resource-management (SHRM). These categories were refind according to historical and contemporary-literature. Using theoretical-sensitivity and directed by the data, a modified-version of complex-adaptive-system (CAS) with its characteristics of non-linearity and adaptation expressed how the data behaved. As the data were being analysed a definite-sense of movement was apparent. The researches when studied the relationships among functions which turn to be more-adaptive than linear. Using non-linear-theories urges the researchers further develop new-theories in human resources.Â Keywords:Â PA, HRM, SHRM, transition, modified-CAS